THE ROLE OF DIGITAL TECHNOLOGIES IN RESEARCH MANAGEMENT: TRANSFORMING EDUCATIONAL RESEARCH COMMUNITIES AND SOCIAL NETWORKS - Tuerah, Paulus Robert; Retor, Wanda Melisa Guendoline; Najoan, Yunita Angelin; Malonda, Natalia Livindi; Mewoh, Angeline Lasya; Kakomole, Imelda; Sumual, Tinneke Evie Meggy (Labor Program Studi Pendidikan Sosiologi, 2023)
This study explores the profound impact of digital technology on educational research management through a comprehensive qualitative literature review. The research aims to analyze how digital infrastructure transforms knowledge production, collaboration, and dissemination in educational research communities. Utilizing systematic literature review methods, the study examines academic databases from 2010-2023, employing qualitative meta-synthesis techniques to identify emerging patterns and themes. The findings reveal three critical transformations: (1) the emergence of dynamic, networked research ecosystems that transcend traditional institutional boundaries; (2) the democratization of knowledge through digital platforms that enable more inclusive and participatory knowledge production; and (3) the complex ethical challenges arising from digital research infrastructures. Theoretical perspectives from Social Network Theory, Actor-Network Theory, Digital Public Sphere Theory, and Critical Pedagogy provide nuanced insights into these transformations. The study demonstrates that digital technology is not merely a tool but an active mediator reshaping epistemological practices, social relations, and research governance. Recommendations include developing adaptive ethical protocols, creating flexible research infrastructures, and fostering digital literacy among researchers. The research contributes to understanding the fundamental shifts in educational research management in the digital age.